Motivational interviewing training for caregiver counsellors: Study protocol of a mixed-methods evaluation using the Kirkpatrick model - Schmidt, Johanna; Bösl, Sophia; Lauer, Natascha; Grässel, Elmar; Henßler, Oliver Timo; Pendergrass, Anna (BMJ Open, 2025)
Introduction Caring for a relative in the home environment is a great challenge for many informal caregivers (CGs). Caregiver counselling offers support to the CGs and can, thus, help them improve CGs' burdensome home care situations, especially if the caregiver counsellors (CCs) have good communication skills. Motivational interviewing (MI) has the potential to further enhance the communication skills of CCs and the effectiveness of MI has been demonstrated internationally in a wide variety of contexts. However, MI has not been implemented and evaluated in the caregiver counselling context yet. Methods and analysis The goals of our prospective, interventional, mixed-methods study are the development, implementation and evaluation of a training course for CCs on the topic of 'Motivational Interviewing for caregiver counselling' in Germany. The training is specifically adapted to the caregiver counselling context and consists of an e-Learning, an on-site workshop and a voluntary follow-up support phase. Its quality and benefits will be evaluated according to Kirkpatrick's four-level evaluation model. Measured outcomes will be participants' satisfaction with the training (level I: reaction), MI knowledge (level II: learning), perceived use (level III: behaviour) and counselling competence, self-efficacy, social cognitions about the use of MI and perceived impact of MI (level IV: results). Primary outcome is counselling competence measured by Counsellor Activity Self-Efficacy Scale. The data will be collected at baseline (t 0), after the on-site workshop (t 1), after the voluntary follow-up support (t 2) and 6 months after the training (t 6). Quantitative data will be analysed with several repeated-measures ANOVAs and qualitative data with qualitative content analysis. Recruitment is ongoing until 31 July 2024. Ethics and dissemination All procedures were approved by the Ethics Committee of the Friedrich-Alexander University Erlangen-Nürnberg (project number 24-108-B). Informed consent will be obtained before participants are enrolled. Serious adverse events are not expected. Results will be published in peer-reviewed journals and presented at conferences. Trial registration number ISRCTN14218056.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Caregiver Burden; Caregivers; Psychosocial Intervention; Quality in healthcare